Influence of BclI C/G (rs41423247) on hippocampal shape and white matter integrity of the parahippocampal cingulum in major depressive disorder. (October 2016) - Won, Eunsoo; Kang, June; Kim, Aram; Choi, Sunyoung; Han, Kyu-Man; Tae, Woo Suk; Chang, Hun Soo; Son, Kyu Ri; Greenberg, Tsafrir; Joe, Sook-Haeng; Lee, Min-Soo; Ham, Byung-Joo
Highlights: Interactive effects of Bcl I C/G (rs41423247) and major depression diagnosis on hippocampal shape and cingulum integrity were investigated. Fifty-two patients with major depression and 52 healthy controls underwent T1-weighted structural magnetic resonance imaging and genotyping. Hippocampal shape was analyzed by FIRST module of FSL and white matter integrity by diffusion tensor imaging and tract-based spatial statistics. Bcl I minor (G-) allele carrier patients showed left hippocampal shape alterations compared to minor allele carrier healthy controls (HCs). Minor allele carrier patients showed decreased left parahippocampal cingulum fractional anisotropy compared to minor allele carrier HCs. Abstract: We investigated the interactive effects of Bcl I C/G (rs41423247) allelic variants and the diagnosis of major depressive disorder (MDD) on hippocampal shape and integrity of the left parahippocampal subdivision of the cingulum. Fifty-two patients with MDD and 52 healthy controls (HCs) underwent T1-weighted structural magnetic resonance imaging and Bcl I C/G (rs41423247) genotyping. We analyzed hippocampal shape using the FIRST module of FSL and analyzed white matter (WM) integrity using diffusion tensor imaging (DTI) and tract-based spatial statistics (TBSS). Significant alterations in left hippocampal shape and decreased fractional anisotropy (FA) values of the left parahippocampal cingulum were observed in MDD patients, compared to HCs. In addition, MDD patients of the Bcl I minor (G-) allele carrier group showed significant alterations in left hippocampal shape and decreased FA values of the left parahippocampal cingulum compared to Bcl I minor (G-) allele carrier HCs. No significant differences between diagnostic subgroups of the C/C homozygotes were observed. Our study provides evidence for alterations in hippocampal shape and decreased integrity of the WM region associated with the hippocampus in MDD, and for the possible influence of Bcl I C/G polymorphism (rs41423247) on hippocampal shape and integrity of the parahippocampal subdivision of the cingulum in depression.